IMPLEMENTASI WIRELESS SENSOR NETWORK PROTOTYPE SEBAGAI FIRE DETECTOR BERBASIS ANDROID MENGGUNAKAN PUSH NOTIFICATION - Asril Azhar; Isnawaty Isnawaty; Subardin Subardin (semanTIK, 2019)
A fire detector is a device that serves to provide a signal or danger signal if there is a potential for fire. The Wireless Sensor Network (WSN) system that is implemented in this fire detector is built to detect fires in the form of smoke, gas, and temperature. The sensors used are smoke sensors (MQ-2) and temperature sensors (DHT11). This tool detects fires using sensors connected to the NodeMCU microcontroller. The detection data is then sent to Firebase continuously and sends push notifications to users or users in real time. The fire detector tool is able to detect early symptoms in a fire if the smoke sensor is worth 1 while the temperature sensor is worth above 30°C. From the results of the research obtained the success of the user receiving notifications is very dependent on the internet connection and the sensors used.Keywords—Fire Detector, Wireless Sensor Network, NodeMCU, Firebase DOI : 10.5281/zenodo.2636989